(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
Cyber Forensics is a branch of forensic science that is aimed to restore, collect and examine the digital evidence of materials found in digital devices, in relation to cybercrimes. With the advancement in cyber area, frequent use of internet and technologies leads to cyber-attacks. Cyber forensic is opted for acquiring electronic information and investigation of malicious evidence found in system or on network in such a manner that makes it admissible in court. It is also used to recover lost information in a system. The retrived information is used to prosecute a criminal. Number of crimes committed against an internet and malware attacks over the digital devices have increased. This paper contains a brief review of the literature aimed to identify the relevant pieces of knowledge in the digital forensics field.